Liquidity Risk Management in Corporate Finance: Strategies for Financial Resilience - Adzka Rosa Sanjayyana; Irsyad Kamal; Muhammad Rispan Affandi; Medeilia Bernike Br Ginting; Abdul Rosid (Jurnal Informasi dan Teknologi, 2025)
Liquidity risk management is one of the crucial aspects in maintaining the operational continuity and financial stability of companies. This study aims to explore various strategies employed by Indonesian companies in managing liquidity risk, as well as their impact on financial resilience. The main focus of this research includes cash flow management, financing source diversification, technology utilization, debt management, and the use of hedging strategies. The research findings show that companies with effective liquidity management strategies, such as the use of cash flow projections and cloud-based technology, are more resilient in uncertain market conditions. Furthermore, financing diversification through revolving credit, capital markets, and equity provides flexibility in accessing the necessary funds during liquidity crises. Managing debt with a balance between short-term and long-term debt also plays an important role in reducing liquidity pressure. On the other hand, hedging against exchange rate and interest rate fluctuations using derivative instruments helps companies mitigate external risks that could affect their liquidity. The study concludes that the implementation of these strategies is essential in maintaining liquidity stability and the competitiveness of companies in the face of global economic challenges. Therefore, companies need to develop adaptive and sustainable liquidity management policies to face future economic uncertainties.